2016
DOI: 10.1038/srep37717
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic SATB1 induces paracrine activation of hepatic stellate cells and is upregulated by HBx

Abstract: Chronic hepatitis B virus (HBV) infection is a major cause of chronic liver diseases, but its involvement in hepatic fibrogenesis remains unclear. Special AT-rich binding protein 1 (SATB1) has been implicated in reprogramming chromatin organization and transcription profiles in many cancers and non-cancer-related conditions. We found that hepatic SATB1 expression was significantly up-regulated in fibrotic tissues from chronic hepatitis B virus (HBV)-infected patients and HBV transgenic (HBV-Tg) mouse model. Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…However, in contrast to HCV, the direct involvement of HBV infection in HSC activation remains less defined. A recent study showed that the HBV encoded x protein (HBx) induces overexpression of the special AT-rich binding protein 1 (SATB1) in hepatocytes, which in turn promotes the activation and proliferation of HSCs through the secretion of CTGF and PDGF [193]. Moreover, Liu et al observed that HBV can transiently infect and replicate in cultured HSCs in-vitro and that production of HBV S protein (HBs) affects their proliferation and expression of collagen type I [194].…”
Section: Chronic Hepatitis Bmentioning
confidence: 99%
“…However, in contrast to HCV, the direct involvement of HBV infection in HSC activation remains less defined. A recent study showed that the HBV encoded x protein (HBx) induces overexpression of the special AT-rich binding protein 1 (SATB1) in hepatocytes, which in turn promotes the activation and proliferation of HSCs through the secretion of CTGF and PDGF [193]. Moreover, Liu et al observed that HBV can transiently infect and replicate in cultured HSCs in-vitro and that production of HBV S protein (HBs) affects their proliferation and expression of collagen type I [194].…”
Section: Chronic Hepatitis Bmentioning
confidence: 99%
“…HBx induces severe lipid accumulation in HBx-Tg hybrid mice [38], and alters the production of ECM by modulating the expression of membrane-type matrix metalloproteinase-1 and fibronectin [53,54]. More convincing evidence is the induction of liver fibrosis in HBV and HBx Tg mice exposed to carbon tetrachloride (CCl4) [55][56][57]. Gong et al [57] reported that SATB1 expression is significantly up-regulated in liver fibrotic tissues from HBV chronic patients and HBV Tg mouse model, and knockdown of SATB1 in the liver significantly alleviates the fibrosis induced by CCl4 exposure in the HBV-Tg mouse model.…”
Section: Hbx Enhances the Development Of Liver Fibrosis In Tg Micementioning
confidence: 99%
“…More convincing evidence is the induction of liver fibrosis in HBV and HBx Tg mice exposed to carbon tetrachloride (CCl4) [55][56][57]. Gong et al [57] reported that SATB1 expression is significantly up-regulated in liver fibrotic tissues from HBV chronic patients and HBV Tg mouse model, and knockdown of SATB1 in the liver significantly alleviates the fibrosis induced by CCl4 exposure in the HBV-Tg mouse model. Increased expression of SATB1 in hepatocytes enhances the activation and proliferation of hepatic stellate cells (HSCs) by secreting connective tissue growth factor (CTGF), Interleukin-6 (IL-6) and platelet derived growth factor-A (PDGF-AA).…”
Section: Hbx Enhances the Development Of Liver Fibrosis In Tg Micementioning
confidence: 99%
See 1 more Smart Citation
“…We then designed a series of in vitro and in vivo studies to observe whether HBV induced HCC progression via enhancement of the expression and secretion of ENPP2. Finally, since in liver tissue HBV infection not only transforms host cell hepatocytes and activates HSC through viral antigens (Martin-Vilchez et al, 2008;Zan et al, 2013;Gong et al, 2016;Zhang et al, 2020) and possibly through ENPP2 from hepatocytes (Kaffe et al, 2017), we analyzed the role of activated HSC (aHSC) in HBV-related HCC progression. These data can improve our understanding of the molecular mechanisms in HBV-related HCC malignancy.…”
Section: Introductionmentioning
confidence: 99%